2021
DOI: 10.1038/s41550-021-01532-8
|View full text |Cite
|
Sign up to set email alerts
|

Probable detection of an eruptive filament from a superflare on a solar-type star

Abstract: Solar flares are often accompanied by filament/prominence eruptions (~104 K and ~1010−11 cm−3), sometimes leading to coronal mass ejections that directly affect the Earth’s environment1,2. ‘Superflares’ are found on some active solar-type (G-type main-sequence) stars3–5, but the filament eruption–coronal mass ejection association has not been established. Here we show that our optical spectroscopic observation of the young solar-type star EK Draconis reveals evidence for a stellar filament eruption associated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
143
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 83 publications
(157 citation statements)
references
References 68 publications
13
143
0
1
Order By: Relevance
“…Through this campaign, we succeeded in obtaining optical spectroscopic data of two superflares on a solar-type star, simultaneously with TESS photometry. One event on April 5, 2020 was already reported by Namekata et al (2021), and another event on March 14, 2020 will be reported in this Letter.…”
Section: Observations and Analysismentioning
confidence: 60%
See 4 more Smart Citations
“…Through this campaign, we succeeded in obtaining optical spectroscopic data of two superflares on a solar-type star, simultaneously with TESS photometry. One event on April 5, 2020 was already reported by Namekata et al (2021), and another event on March 14, 2020 will be reported in this Letter.…”
Section: Observations and Analysismentioning
confidence: 60%
“…The exposure time was set to be 30 sec for these nights. The data reduction follows the prescription in Namekata et al (2020bNamekata et al ( , 2021 with IRAF and PyRAF packages. Only the data of particular interest are shown in Figure 2.…”
Section: 8-m Seimei Telescopementioning
confidence: 99%
See 3 more Smart Citations